Strengthening financial system regulation: The Nigerian case - Godwin E. Uddin; Anthony O. Monehin; Emeka Osuji (International Journal of Management, Economics and Social Sciences (IJMESS), 2020)
Many studies have considered the efficacy of the Central Bank of Nigeria (CBN)'s monetary policy to ensure Deposit Money Banks (DMBs) performance in Nigeria but scantily mentioned in literature are assertions on other roles that the Asset Management Corporation of Nigeria (AMCON) - an agency aligned to the CBN, could perform to further strengthen the efficacy of the CBN's monetary policy (and/or macro/microprudential guidelines) in financial sector management, even so during this COVID-19 pandemic and afterward, and besides AMCON's statutory role of debt recovery. Also, the need for initiatives that could inform efforts to strengthen the efficacy of CBN's policy instruments, despite post-2010 debt-recovery activities by AMCON, remains. Thus, this review article examines the activities of AMCON and their implications on CBN's policy instruments design/formulation and implementation in Nigeria. Our findings thereof include AMCON contributes to DMBs' surveillance which could inform CBN's policy instruments design/formulation, and that the basis of the association between CBN and AMCON is prominent in respect to policy instruments' implementation and compliance. Therefore, this study recommends CBN to leverage on AMCON's recurrent interface with DMBs to further strengthen the operational effectiveness of so established policy instruments.
Keywords: E5; E52; E58; G28; 330; Monetary policy; Deposit Money Banks (DMBs); Central Bank of Nigeria (CBN); Asset Management Corporation of Nigeria (AMCON); Coronavirus (COVID-19)